The Role of Regular Teachers in Guiding Children with Special Needs and Slow Learner Learning Difficulties in Elementary Schools - Aprilia Dwi Kurnia Utomo; Utami, Ratnasari Dyah (Universitas Pendidikan Ganesha, 2024)
Inclusive education allows learner children with special needs to obtain equal education in a public school environment. This research aims to analyze the role of teachers in regular classes in guiding children who face learning difficulties as slow learners. The type of research is descriptive qualitative, with participants consisting of class teachers, subject teachers, and slow-learner children. Data analysis methods are used through interviews, observation, and documentation. Validity of information through source triangulation techniques. Data analysis involves collecting information, data reduction, data presentation, and conclusion. The findings from this research are that educators in the classroom have four core roles in the teaching and learning process, namely as demonstrators, class managers, mediators and facilitators, and evaluators. These four functions have close reciprocity in achieving optimal learning achievement. However, teachers also need help with the learning process, including slow-learning students who experience obstacles in absorbing lesson material, communication difficulties, low concentration, difficulty completing assignments, or delays in submission. This research concludes that educators have four leading roles in optimizing learning effectiveness. This research implies that teachers can perform well in the learning process.